PENERAPAN FIQH JUAL BELI DAN TRANSAKSI DI MEDIA SOSIAL - Siti Trizuwani; Muhamad Zen (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
This research aims to analyze the buying and selling processes occurring on social media from the perspective of contemporary fiqh muamalah. The method used is library research approach to examine issues related to transactions on social media. The author also applies Islamic law to determine the legal ruling on buying and selling through social media. The problem addressed in this study concerns transactions conducted online via social media. Although online transactions make buying and selling easier, it cannot be denied that they also have their drawbacks. The findings of this research indicate that contemporary transactions are no longer reliant on face-to-face interactions but have evolved with the rise of online buying and selling